An integrated marketing communication strategy to increase a number of inpathent visits at Efarina Etaham Hospital Berastagi - Zerry All Vindo Tarigan; Ali Napiah Nasution; Chrismis Novalinda Ginting (SEAN Institute, 2024)
Health, as a human right, requires fair, equitable, and quality services for the entire community. The Indonesian government is committed to improving health by providing facilities, including hospitals. The Health Law emphasizes the right of every individual to access safe and affordable health care. Hospitals play a strategic role in improving public health, but have evolved into